Determining the Synthesis, Chemical Modification and Biological Properties of N-acylphenothiazines - Myrko, Iryna; Chaban , Taras; Matiichuk, Yulia; Arshad , Mohammad; Matiychuk, Vasyl (Current Topics on Chemistry and Biochemistry Vol. 1, 2022)
Theoretical and experimental data concerning the versatile approaches for the synthesis of N-acylphenothiazines were systematized in this review. The aim of this research was to compile the literature reported worldwide in the past 20 years. The pharmacological effects of these heterocycles as one of the promising chemotherapeutic goals for modern bioorganic and medicinal chemistry were also reviewed in this article. The radical character of the acyl moiety is thought to be responsible for these moieties' immense biological potential. As a result, the current study will make a valuable contribution to the literature and will serve as a springboard for medicinal chemistry experts to conduct additional research focusing on N-acylphenothiazine moieties as potential chemotherapeutic drugs.